An Entrepreneurial Perspective on Managing Microenterprises: Issues and Challenges (Trinity Journal of Management, IT & Media (TJMITM), 2022)
This article elaborates the outcome of a descriptive study aimed at understanding the emergence of successful entrepreneurs and owners of micro-enterprises in rural India. Based on the four case studies of village-based entrepreneurs drawn from the state of Tamil Nadu of India, this article examines the socio-economic profile of the entrepreneurs, their drive for shifting to non-farm based activity, their method of resource generation and the means of sustaining the passion in running the enterprise and the factors that facilitated entry of the village-based entrepreneurs into a business activity. The focus is shifting on micro enterprise and small business for their contribution towards the economic development of a Country. Its role may not be as big as the large corporate houses, yet its potential to generate employment coupled with meagre resources and limited infrastructure and ability to meet the challenges is the primary focus of this study. The cumulative effect of all the micro enterprises put together is worth mentioning. Attention is not lost on the contribution of women in this sector. Any enhancement in entrepreneurial activity will have a bearing on the development of the society at large. It is expected that tapping on entrepreneurial potential is going to yield rich dividends. Not to mention its role in fostering the phase of socio economic development, wealth creation, employment generation, local economic development and poverty reduction. Women are culturally well equipped to run their business due to innate skill developed through managing households, and multi-tasking. In spite of numerous challenges, irrespective of the strata, more women are entering into the field of entrepreneurship. A conceptual framework is suggested for effective management of a microenterprise. Leveraging technology and its advancements to advantage are also dealt with. Ignorance, need for upskilling on the part of entrepreneurs and banks are some of the factors inhibiting their progress. Similarly other challenges and opportunities are brought out along with remedial actions. Implications for managers and practitioners are discussed.
Keywords: Cipher text; multi keyword; parallel retrieval and encryption